Ankylosis of temporomandibular joint in children - Das U; Keerthi R; Ashwin D; VenkataSubramanian R; Reddy D; Shiggaon N (Wolters Kluwer Medknow Publications, 2009)
Background: Temporomandibular joint (TMJ) ankylosis or hypomobility involves fusion of the mandibular condyle to the base of the skull. It is a major clinical problem that affects many patients suffering from facial trauma, infection, or systemic disease. The treatment of TMJ ankylosis poses a significant challenge because of technical difficulties and a high incidence of recurrence. Case Report: This report describes a case of a 4-year-old boy with inability to open mouth, diagnosed with unilateral right bony TMJ ankylosis. The surgical approach consisted of gap arthroplasty followed by vigorous physiotherapy. Conclusion: A detailed history, clinical and functional examination, radiographic examination facilitating correct diagnosis followed by immediate surgical intervention, and physiotherapy can help us to restore physical, psychological, and emotional health of the child patient.